Right-sided Decortication in a Patient with Left Pulmonary Artery Embolism – A Case Report - Meshram, Tanvi; Rathod, Darshana; Kumari, Kamlesh K.; Sahayraja M, Arun (Nepalese Medical Journal, 2022)
This case is an anesthesia challenge and management of one-lung ventilation in a patient with pulmonary embolism of the ventilated lung. A 50 years old male with a history of pulmonary thromboembolism of segmental and subsegmental branches of the left pulmonary artery was posted for right decortication. He developed hypoxia (sp02 82-85% ) and PaC02-EtCO2 difference of 30 mm Hg on initiation of one lung ventilation indicating significant shunting of blood and V/Q mismatch. We want to emphasize the importance of intraoperative arterial blood analysis to look for (PaCO2 –EtCO2) difference and periodic reinflation of the collapsed lung for management of patients in whom the blood supply to the dependent is compromised. The presence of pulmonary vascular compromise on the dependent side offers a great number of challenges during the management of one-lung ventilation.